The Effect of the School Literacy Movement Program on Student Learning Outcomes in Economics Subjects - Novita, Yulia; Mukhtar, Nurkamelia; Salmiah, Salmiah (Universitas Islam Negeri Sultan Syarif Kasim Riau Pekanbaru, 2024)
This research was instigated by students who did not yet understand what literacy was, so they did not understand the literacy process in the learning. This research aimed at knowing the influence of school literacy movement program toward student learning achievement on Economics subject at the eleventh grade of State Senior High School 2 Bangkinang City, Kampar Regency. Quantitative descriptive method was used to achieve the goal. All of the eleventh-grade students of Social Science at State Senior High School 2 Bangkinang City were the population of this research, and they were 120 students. Random sampling technique was used in this research, and 30 students were selected as the samples. Questionnaire and documentation were the techniques of collecting data. Validity and reliability test were used to test the instruments. Descriptive data analysis technique, changing ordinal data to interval, linearity test, and simple linear regression were used to analyze the data. Based on the analysis result, it was obtained that robserved was higher than rtable at 5% and 1% significant levels (0.3610<0.762>0.4629). It meant that there was a significant influence of school literacy movement program toward student learning achievement on Economics subject. The contribution level was 52.8%, and the rest 42.8% was influenced by other variables.